Supplementation of Ampelopsis grossedentata extract contributes to the improvement of intestinal health in swine - Liu, Xiangyan; Zhang, Fusheng; Li, Mengyao; Li, Rong; Zhang, Zhen; Xu, Juan; Wen, Lixin; Li, Rongfang (Frontiers in Veterinary Science, 2024)
Ampelopsis grossedentata (Vine tea), a high polyphenol content antioxidant plant resource, is renowned for its medicinal benefits. This study aimed to investigate the effects of Ampelopsis grossedentata extract (AGE) on anti-inflammatory and antioxidant ability, enhancement of intestinal immunity, improvement of intestinal structure, and regulation of gut microbiota in swine. 135 weaned piglets were randomly divided into three groups: a control group, a low-dose group, and a high-dose group.Pigs were weighed and taken blood on days 36, 85, and 154. The feed intake was recorded daily to calculate growth performance parameters. On day 154, five to six pigs in each group were randomly selected and euthanized to obtain a small intestine to investigate the effects of Ampelopsis grossedentata extract (AGE) on antiinflammatory and antioxidant ability, and gut microbiota. The results showed that 500 mg/kg AGE increased the expression of Anti-inflammatory and immune cytokines (IL-10, IgG, and IgA) (P < 0.05, P < 0.01), and decreased the expression of proinflammatory cytokines (IL-1β) (P < 0.05) in serum. Additionally, 500 mg/kg AGE enhanced the antioxidant capacity by increasing the GSH-Px, CAT, and SOD (P < 0.05, P < 0.01). 500 mg/kg AGE significantly increased the abundance of gut microbiota, enhanced the gut barrier and modulated gut immunity. During the piglet phase, 500 mg/kg AGE increased the relative abundance of Prevotella (P < 0.05). During the growing-finishing phase, 500 mg/kg AGE increased the relative abundance of unclassified_f__Lachnospiraceae and Bacteroides (P < 0.05, P < 0.01). Overall, we recommended 500 mg/kg AGE as a routine addition dose for swine to improve porcine growth performance and intestinal health.